2019
DOI: 10.1021/acs.energyfuels.9b01166
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Environment-Friendly Natural Extract for Inhibiting Shale Hydration

Abstract: This paper reports the first use of Tribulus terrestris extract (TTS), a newly developed nonionic surfactant, as an inhibitor for shale hydration. The critical micelle concentration of TTS was determined using the surface tension method, while its inhibition properties were evaluated with a variety of inhibition assessment methods. The sodium bentonite inhibition tests revealed that TTS can significantly inhibit clay pulping. The scanning electron microscopy images of unmodified and TTS-modified shale samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Figure 1 shows the FT-IR of PNBAM. As shown in Figure 1 , the stretching vibrational peaks of the N–H, C=O, and C-N bonds present in the amide group occur at 3562, 1683, and 1172 cm −1 , respectively [ 34 , 35 , 36 ]. The stretching vibration peaks of –CH 3 and –CH 2 in the isopropyl group appear at 3080 and 2980 cm −1 , respectively, and the bending vibration peak appears at 1458 cm −1 [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the FT-IR of PNBAM. As shown in Figure 1 , the stretching vibrational peaks of the N–H, C=O, and C-N bonds present in the amide group occur at 3562, 1683, and 1172 cm −1 , respectively [ 34 , 35 , 36 ]. The stretching vibration peaks of –CH 3 and –CH 2 in the isopropyl group appear at 3080 and 2980 cm −1 , respectively, and the bending vibration peak appears at 1458 cm −1 [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Guancheng et al evaluated the shale inhibition performance of the cationic polymer polyethyleneimine (PEI) with different molecular weights and reported that PEI has better performance than other inhibitors widely applied in the oil field. Besides, other shale inhibitors such as biomaterials and nanoparticles also attracted intensive attention in the research field. However, for highly reactive shale formation, the available shale inhibitors could not meet the requirements of on-site engineering.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 The search for monomeric organic compounds from natural extracts, with shale inhibition potentials similar to or better than the conventional clay stabilizers, like KCl, is on the rise. 35 These compounds should be biodegradable, nontoxic, less expensive, and easily accessible. 36 A present research goal is to develop effective ultra-lowmolecular-weight stabilizers capable of satisfying the environmental regulation rules for aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Again, the move toward compounds that leave little or no environmental footprints is increasing due to the stringent rules from environmental agencies. , The search for monomeric organic compounds from natural extracts, with shale inhibition potentials similar to or better than the conventional clay stabilizers, like KCl, is on the rise . These compounds should be biodegradable, nontoxic, less expensive, and easily accessible .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation